A Family Systems Perspective on Supporting Self-Determination in Adults with Intellectual Disabilities During Transitions - Taylor, Whitney Dawn (Université d'Ottawa / University of Ottawa, 2019)
This dissertation concerns the family context of self-determination in adults with intellectual disabilities (ID) during life transitions. Although self-determination is interpreted in different ways in different disciplines, the construct is frequently used to describe the attitudes and behaviours that allow people to feel autonomous and causal in their lives. Research on self-determination in adolescents and adults with ID has commonly occurred in community and special education sectors, with an emphasis on arranging supports for people with ID to develop component self-determination skills, like choice making, problem solving, and goal setting. From the perspective of organismic-dialectical theories, people develop and express self-determination through relationships and person-environment interactions at multiple system levels. Further research on the way family interactions and supports influence the self-determination of adults with ID is important. To address this need, this dissertation includes a qualitative study presented in two manuscripts and a quantitative study presented in one manuscript. The qualitative study explored processes and challenges in the family system during significant life transitions with an adult family member with ID. Families participated in semi-structured interviews and ethnographic observations of daily activities every three to four months for one year. Manuscript 1 concerns the influence of family processes on the self-determination of two young adults with ID as they attained adult roles in the community. Parents were observed to model goal setting, encourage choice making, and scaffold new skills, which helped the young adults with ID to experience autonomous motivation in their transitions. Parents reported feeling unsure of the best way to promote their adult child’s independence while ensuring his or her safety. They tried to resolve this dilemma with open and honest communication. Most interestingly, families collaborated in choice making to the extent that every family member perceived autonomy in transition planning and implementation. Manuscript 2 concerns the influence of transition processes and challenges on the quality of life and resilience of four families with an adult family member with ID. Although families reported different transition types, they progressed through similar transition stages. They invested in quality of life and self-determination as a foundation, considered future support needs, pre-planned and actively planned transitions, implemented transitions, adjusted to new roles and routines, and reflected upon their growth. Although all families experienced challenges during their transitions, two families entered a state of crisis when they did not receive mental health and residential supports. Findings highlight that transitions are lifelong processes in the family system, and risk and protective factors at multiple system levels affect resilience and self-determination. The quantitative study, presented in Manuscript 3, considers that the family system functions within broader socioecological environments that include formal services for adults with ID. Community participation supports provide opportunities to develop self-determination in recreational, educational, and vocational activities. In a cohort of families requesting community participation supports, the vast majority of parents endorsed the expectation that this service would improve choice-making outcomes for their adult child with ID. Preliminary results suggest that the gender and prior choice-making experience of the adult with ID may be associated with the odds of parents endorsing this expectation. The General Discussion integrates the primary findings from each manuscript within a conceptual framework informed by self-determination theory, family systems theory, and family resilience models. This dissertation has theoretical implications for the way the self-determination construct is understood and applied in research with families with a family member with ID. Further, this dissertation reveals practical implications for supporting families with a family member with ID during important life transitions.
Keywords: intellectual and developmental disabilities; family systems theory; self-determination theory; family resilience; choice making; transition to adulthood; transition to supported independent living; access to services